2011
DOI: 10.1603/en10170
|View full text |Cite
|
Sign up to set email alerts
|

Leafminer Fly (Diptera: Agromyzidae) Occurrence, Distribution, and Parasitoid Associations in Field and Vegetable Crops Along the Peruvian Coast

Abstract: Leafminer ßies (Diptera: Agromyzidae) are important agricultural pests worldwide. The objective of our study was to assess the relative importance of agromyzids and their associated parasitoids in Þeld and vegetable crops along the Peruvian coast. In total, nine leafminer ßy species were identiÞed in 27 crops. The most dominant species was Liriomyza huidobrensis (Blanchard) (88.0%). Liriomyza sativae Blanchard was the second most dominant species (8.59%) but mainly found in the most northern part of Peru. On a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 38 publications
(35 reference statements)
1
42
0
2
Order By: Relevance
“…as parasitoids of Liriomyza spp. in the USA and South America (Trumble ; Neder de Roman , Mujica & Kroschel ; Muchemi et al . ).…”
Section: Parasitoids Of Australian Agromyzidaementioning
confidence: 99%
“…as parasitoids of Liriomyza spp. in the USA and South America (Trumble ; Neder de Roman , Mujica & Kroschel ; Muchemi et al . ).…”
Section: Parasitoids Of Australian Agromyzidaementioning
confidence: 99%
“…(Johnson & Hara ; Waterhouse & Norris ; Minkenberg ; Johnson ; Liu et al. ; Cisneros & Mujica ; Mujica & Kroschel ). Successful control of leaf miner species through migration of Diglyphus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Head et al (2000) reported the potential of using an entomopathogenic nematode Steinernema feltiae, in combination with chemical pesticides in an integrated pest management (IPM) programme against the pest. In the pest's native habitat, a complex of more than 60 parasitoid species were found associated with and keeping the pest under economic threshold (Murphy & La Salle 1999;Mujica & Kroschel 2011). The International Centre of Insect Physiology and Ecology (ICIPE) has imported three most promising of those parasitoids; (Phaedrotoma scabriventris Nixon (Braconidae: Opiinae), Halticopera arduine (Walker) (Hymenoptera: Pteromalidae) and Chrysocharis flacilla Walker (Hymenoptera: Eulophidae)) from Peru (where they have been reported to cause mortality of between 20 and 52 %) and introduced into ICIPE's quarantine facilities for an IPM programme in Kenya (Mujica & Kroschel 2011;Chabi-Olaye et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the pest's native habitat, a complex of more than 60 parasitoid species were found associated with and keeping the pest under economic threshold (Murphy & La Salle 1999;Mujica & Kroschel 2011). The International Centre of Insect Physiology and Ecology (ICIPE) has imported three most promising of those parasitoids; (Phaedrotoma scabriventris Nixon (Braconidae: Opiinae), Halticopera arduine (Walker) (Hymenoptera: Pteromalidae) and Chrysocharis flacilla Walker (Hymenoptera: Eulophidae)) from Peru (where they have been reported to cause mortality of between 20 and 52 %) and introduced into ICIPE's quarantine facilities for an IPM programme in Kenya (Mujica & Kroschel 2011;Chabi-Olaye et al 2013). Implementing an IPM programme and/or developing an efficient mass-rearing procedure will, however, require the understanding of how L. huidobrensis selects host plants for feeding and oviposition and ultimately how the host plants support its survival.…”
Section: Introductionmentioning
confidence: 99%